A PEEK Rod-Based Dynamic Instrumentation Construct for the Degenerative Lumbar Spine Disease, First Appraisal Based on Five-year Clinical and Radiological Findings - Anghel A; Garthmann J; Alkahwagi B (Medical Devices: Evidence and Research)
Andrei Anghel, Jonas Garthmann, Baraa Alkahwagi Spine Unit, Orthopaedic Clinic Hessisch Lichtenau, Hessisch Lichtenau, Hessen, GermanyCorrespondence: Andrei Anghel, Spine Unit, Orthopädische Klinik Hessisch Lichtenau, Am Mühlenberg 17, Hessisch Lichtenau, 37235, Germany, Tel +4915231760951, Email AAnghel@lichtenau-ev.dePurpose: The present retrospective study delivers first results after the use of a pedicle based, screw and peek rod system. Emphasis was placed on the ability of the construct to prevent adjacent segment disease at an average of 5 years follow-up by maintaining a certain degree of movement in the index segment. This was evaluated via functional X Rays before and after surgery.Patients and Methods: The cohort comprised 100 patients which received decompressive surgery in one or more segments with dynamic instrumentation for stenosis of the lumbar spinal canal and degenerative spondylolisthesis. We analyzed diagnostic imagery including functional X Rays prior and after surgery as well as cohort demographics such as reoperation rate, complications and overall patient satisfaction.Results: The average age was 68 years, at 58 months follow-up there were 43 cases of radiological adjacent segment disease. We defined a radiological ASD as an increase of the osteoarthritis on the Wiener scale and stenosis of the spinal canal on the MRI scans. In our cohort 80 patients benefited from the surgery, either being pain free or having improved symptoms at the mean follow-up with the others either requiring renewed surgery or having developed clinically significant ASD. There was no significant statistical correlation between area of spinal canal, gender and outcome.Conclusion: In one segment constructs the system being evaluated showed no major disadvantage when compared to similar non-fusion pedicle-based techniques nor was it able to consequently prevent ASD. Under the clinical point of view there was in our opinion no marked benefit when compared against decompressive surgery and fusion as the accepted standard. Regarding the multi segment instrumentation further larger number studies are needed to reach a conclusion.Keywords: semi constrained screws, dynamic instrumentation, degenerative spondylolisthesis, spinal canal stenosis